2013
DOI: 10.1002/oby.20007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein to carbohydrate balance on energy intake, fat storage, and heat production in mice

Abstract: Objective: Protein leverage plays a role in driving increased energy intakes that may promote weight gain. The influence of the protein to carbohydrate ratio (P:C) in diets of C57BL/6J mice on total energy intake, fat storage, and thermogenesis was investigated. Design and Methods: Male mice (9 weeks old) were provided ad libitum access to one of five isocaloric diets that differed in P:C. Food intake was recorded for 12 weeks. After 16 weeks, white adipose tissue (WAT) and brown adipose tissue (BAT) deposits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 31 publications
7
61
3
Order By: Relevance
“…In our study, the low protein diets contained 67-57% carbohydrates with 33% fat. Others reported that diets relatively high in carbohydrate and fat, similar to the ranges in our study, promoted development of fatty liver and impaired glucose tolerance in both rats [52][53][54] and mice 51 , whereas low protein-high carbohydrate diets increased adiposity and fatty liver with paradoxical improvement in glucose tolerance in mice 6,32,33 . Therefore, despite weight loss with 0P and 5P diets, the increased hepatic lipidosis likely negated any improvements in glucose tolerance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, the low protein diets contained 67-57% carbohydrates with 33% fat. Others reported that diets relatively high in carbohydrate and fat, similar to the ranges in our study, promoted development of fatty liver and impaired glucose tolerance in both rats [52][53][54] and mice 51 , whereas low protein-high carbohydrate diets increased adiposity and fatty liver with paradoxical improvement in glucose tolerance in mice 6,32,33 . Therefore, despite weight loss with 0P and 5P diets, the increased hepatic lipidosis likely negated any improvements in glucose tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to modulating energy intake and expenditure, moderate protein restriction in rats and mice has been consistently associated with alterations in body composition including reduction in lean mass, increased body fat content and development of fatty liver 6,8,9,14,17,32,33 . Protein restricted rats attempt to catch-up on body weight and adipose reserves following refeeding on a standard protein diet [34][35][36][37][38] .…”
mentioning
confidence: 99%
“…Interestingly, this would actually also imply that those who had low intervention points might not be obese but might also be obtaining insufficient supplies of this nutrient. A candidate for the critical nutrient is protein (30,64,66), which is suggested to leverage energy intake when it is supplied at low levels, the "protein leverage" hypothesis. Interestingly, FTO the first gene identified as linked to BMI by GWAS, has been suggested recently to be potentially involved in regulation of protein intake via sensing of essential amino acids (25).…”
Section: So Why Do We Get Fat?mentioning
confidence: 99%
“…The LPHC diet increased energy intake compared to the HPLC diet because of the phenomena of protein leverage, where the protein intake is prioritized over fat and carbohydrate intake [13]. In spite of the increase in the energy intake, the LPHC diet reduced body fat mass because of increased energy expenditure (Table 2), which is consistent with increased diet-induced thermogenesis serving to consume excess energy and slow development of adiposity [14]. This study suggests that a diet replacing carbohydrate with protein may be of little advantage in body fat reduction.…”
Section: A Low Protein-high Carbohydrate Diet Decreases Body Fat In Micementioning
confidence: 75%